2020
DOI: 10.1039/d0ra02156c
|View full text |Cite
|
Sign up to set email alerts
|

Construction of gold-siRNANPR1 nanoparticles for effective and quick silencing of NPR1 in Arabidopsis thaliana

Abstract: Gold nanoparticles (AuNPs) have been widely used as gene silencing agents and therapeutics for treatment due to their high transfection efficiency and lack of cytotoxicity, but their roles in gene silencing in plants have not yet been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…After preparation of PDMAEMA + DNA and PEI + DNA complexes containing 10 μg DNA at a N/P ratio of 15 (total volume 10 μL), it was diluted with 10 mM MgCl 2 /MES with pH 5.7 to a final volume of 200 μL and then infiltrated on the abaxial surface of the leaves using a 1-mL needleless syringe by applying gentle pressure. FAM-siRNA NPR1 (20 μM) ( Lei et al, 2020 ) was mixed with PDMAEMA (1 mg/mL) at the fixed N/P ratio of 15 and incubated at room temperature for 30 min. The formed complexes were diluted 10 times in 10 mM MgCl 2 /MES (pH 5.7) before infiltration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After preparation of PDMAEMA + DNA and PEI + DNA complexes containing 10 μg DNA at a N/P ratio of 15 (total volume 10 μL), it was diluted with 10 mM MgCl 2 /MES with pH 5.7 to a final volume of 200 μL and then infiltrated on the abaxial surface of the leaves using a 1-mL needleless syringe by applying gentle pressure. FAM-siRNA NPR1 (20 μM) ( Lei et al, 2020 ) was mixed with PDMAEMA (1 mg/mL) at the fixed N/P ratio of 15 and incubated at room temperature for 30 min. The formed complexes were diluted 10 times in 10 mM MgCl 2 /MES (pH 5.7) before infiltration.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, functioned gold nanoparticles were used to carry a small interfering RNA and successfully silenced a target gene ( NPR1 ) in Arabidopsis thaliana ( Lei et al, 2020 ). To further explore the transfection behavior of PDMAEMA in plant cells, we combine plasmid GFP (pGFP) as a reporter gene with PDMAEMA and incubated them with protoplasts and leaves to transfect plant cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous reports revealed that AuNPs-PEI-FAM-siRNA NPR1 successfully silenced the function of NPR1 ( Lei et al., 2020 ). Here, we infiltrated healthy periwinkle leaves with AuNPs-PEI-FAM-siRNA NPR1 and used the fluorescence of FAM-siRNA NPR1 to follow the entry of AuNPs-PEI into the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously confirmed that AuNPs-PEI carrying exogenous siRNA NPR1 successfully silenced the NPR1 gene with high specificity ( Lei et al., 2020 ). However, the timing of AuNPs-PEI entry into the cytoplasm and nucleus has not been further investigated.…”
Section: Introductionmentioning
confidence: 89%
“…Nanocomposites not only improve the utilization of drugs, they reduce the usage of drugs and also alleviate environmental pressure. Because we successfully silenced the NPR1 gene using AuNPs carrying siRNA NPR1 ( Lei et al, 2020 ). Our laboratory is developing a nano-genetic technology to activate a defense system for improving resistance by transferring resistant genes to hosts through nanomaterials, hoping to contribute to the prevention and treatment of HLB.…”
Section: Chemical Methodsmentioning
confidence: 99%